DRESS syndrome in a patient with cystic fibrosis: A case report. Issue 4 (14th October 2016) - Gohy, Sophie; Froidure, Antoine; Lebecque, Patrick
Summary: Drug reaction with eosinophilia and systemic symptom (DRESS) syndrome is a rare and severe side‐effect, mainly described after intake of anticonvulsants, allopurinol, or antibiotics. It usually begins within 2 months after drug introduction. Symptoms include cutaneous rash, hematologic abnormalities, and internal organ involvement and the diagnosis might be challenging. This case report illustrates for the first time this life‐threatening complication in a patient with cystic fibrosis (CF). In this case, withdrawal of the offending drug was sufficient for full recovery. Clinicians involved in CF care should be aware of DRESS syndrome, as they commonly prescribe several potentially culprit drugs. Pediatr Pulmonol. 2017;52:E18–E21. © 2016 Wiley Periodicals, Inc.